Present and future integration in Central America. - Salazar, Jose Manuel (1990)
Points out that there are grounds for moderate optimism as regards reinforcing Central American integration in this decade. Proposes the elimination of anti-Central American bias and the promotion of intra-regional trade, for which there are promising prospects.